Profil Kemampuan Representasi Matematis Siswa Sekolah Dasar di Kecamatan Sumedang Selatan - Hani Handayani; Rifahana Yoga Juanda (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
This study aims to determine the profile of mathematical representation ability of elementary school students in South Sumedang District. The research method used is the survey method. The population chosen is the elementary school in South Sumedang District. The sample was chosen randomly, namely six grade V elementary schools in South Sumedang District with a total of 130 students. Based on the results of research on the representation ability of elementary school students in South Sumedang Subdistrict, only 34.6% included the very low category. When viewed per aspect, the verbal representation aspect was 41.2% in the very low category, the symbol representation aspect was 28.1% in the very low category, and in the visual representation aspect it was 34.6% in the very low category.